EFFECTIVE REINFORCING COMPONENT OF IRON-CONCRETE CONSTRUCTIONS IS A STEEL FIBER - I. N. Radjkova; V. I. Gritsaenko; I. V. Kovalj (Литьë и металлургия)
It is shown that use of fiber of the modern material, capable to replace metal reinforcing rod in ferroconcrete, provides decrease of expenses for reinforcing works, increase of degree of production mechanization.